The effect of tethering on the clearance rate of suspension-feeding plankton - Andersen, Anders (Proc Natl Acad Sci U S A, 2020)
Many planktonic suspension feeders are attached to particles or tethered by gravity when feeding. It is commonly accepted that the feeding flows of tethered suspension feeders are stronger than those of their freely swimming counterparts. However, recent flow simulations indicate the opposite, and the cause of the opposing conclusions is not clear. To explore the effect of tethering on suspension feeding, we use a low-Reynolds-number flow model. We find that it is favorable to be freely swimming instead of tethered since the resulting feeding flow past the cell body is stronger, leading to a higher clearance rate. Our result underscores the significance of the near-field flow in shaping planktonic feeding modes, and it suggests that organisms tether for reasons that are not directly fluid dynamical (e.g., to stay near surfaces where the concentration of bacterial prey is high).